1999
DOI: 10.1046/j.1461-0248.1999.00059.x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry as a predictor of growth, fecundity and survival

Abstract: Measures of developmental stability such as fluctuating asymmetry have been assumed to predict individual performance because asymmetry reflects an inability to cope with stressful situations, and because asymmetry hampers locomotion. However, the magnitude of this relationship between important fitness components (growth, fecundity, survival) and asymmetry has never been assessed. Based on a literature survey, estimates of the correlation between asymmetry and the three fitness components are presented. Pears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
3
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 69 publications
1
74
3
1
Order By: Relevance
“…Fat or protein reserves may offer another operational measure of quality but require careful standardisation with respect to breeding stage, as reserve storage and utilisation may depend on the demands imposed by different breeding stages (Moreno, 1989). Fluctuating asymmetry of bilateral traits (Møller, 1999) also has its problems of inter- From studies by Ollason and Dunnett (1988), Coulson (1988a) and Mills (1989).…”
Section: How Can Parental Quality Be Measured?mentioning
confidence: 99%
“…Fat or protein reserves may offer another operational measure of quality but require careful standardisation with respect to breeding stage, as reserve storage and utilisation may depend on the demands imposed by different breeding stages (Moreno, 1989). Fluctuating asymmetry of bilateral traits (Møller, 1999) also has its problems of inter- From studies by Ollason and Dunnett (1988), Coulson (1988a) and Mills (1989).…”
Section: How Can Parental Quality Be Measured?mentioning
confidence: 99%
“…However, floral morphology is important in pollination mechanisms. Petals are a major visual attractant for animal pollinators, and petal size and symmetry are important in pollination processes (Bell 1985;Willson 1990;Møller and Eriksson 1994;Møller 1995;Cronk and Mö ller 1997). Floral traits are more highly canalized than leaves (Bradshaw 1965;Evans and Marshall 1996;Sherry and Lord 1996;Fenster and Galloway 1997;Alados et al 1999;Roy and Stanton 1999), leading to lower sensitivity to stress; i.e., leaves were more asymmetric than petals.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, it is accepted that increased FA is related to genetic and environmental stress (Zakharov 1987;Parsons 1992;Clarke 1993;Graham et al 1993a;Markow 1994;Møller and Swaddle 1997) and poor individual quality (Møller and Pomiankowski 1993;Watson and Thornhill 1994;Markow 1995;Møller and Thornhill 1998). Several studies reported positive correlations between FA and insect herbivory (Møller 1995;Zvereva et al 1997;Martel et al 1999;Lempa et al 2000). Møller (1999b) presented evidence that FA of elm leaves (Ulmus glabra) reflects the susceptibility to disease as well as the negative effect of the disease on phenotypic development.…”
Section: Manuscript Received June 2001; Revised Manuscript Received Jmentioning
confidence: 99%
“…In a literature survey, Møller, (1999) presented the estimates of the magnitude and robustness of the relationship between asymmetry and three fitness components: growth, fecundity, and survival. However, the mean correlation coefficients were relatively small and accounted only for 12.3% of the variance in fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that individuals with a high level of developmental stability have a selective advantage over individuals with lower developmental stability, and therefore developmental stability has been viewed as an integral component of individual fitness (Møller & Swaddle, 1997). The relationship between asymmetry and fitness has been extensively reviewed (Clarke, 1998;Møller, 1999), and several studies have reported a correlation between individual symmetry and fitness components such as fecundity and growth. Positive correlations between FA and environmental stresses have also been observed in various aquatic studies (Alados et al, 2001).…”
Section: Introductionmentioning
confidence: 99%